Hardware architecture for an anti-traffic noise system. Issue 5 (May 2015) - Dhaou, Imed Ben
Abstract This work presents an energy efficient architecture for an anti-traffic noise system. The hardware is designed for a road side unit (RSU) in intelligent transportation systems. Fast Fourier Transform is the cornerstone for the suggested system. An ultra low power architecture for the FFT suitable for FPGA implementation is derived. Bit-widths for both data and twiddle factors are optimized for low-power. The architecture uses an efficient complex multiplier that has 25% less multiplications. An algorithm to compute the number of time-shared butterflies for a given FFT block size and a target throughput is elaborated. Finally synthesis results using fixed-point VHDL library and commercial IP are presented and compared with the proposed FFT processor.